2022
DOI: 10.1111/jep.13665
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of patients and healthcare providers on patient education to improve oral anticoagulant management

Abstract: Rationale and Objectives Education of patients is thought to be key to high‐quality oral anticoagulant (OAC) medication management. Theoretically, improving patients' knowledge should improve their self‐management skills and adherence. The study's objective was to explore the opinions of healthcare providers and patients on the desired content and format of patient education on OACs, in addition to perceived barriers to high‐quality patient education. Methods We applied qualitative descriptive methods in a foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Patient knowledge about the existence of reversal agents, the frequency of physician communication about these agents, and the influence of knowledge about the agents on adherence requires additional exploration, as does the relationship of these interventions on patient adherence. Qualitative work suggests that patients and providers support educating patients about DOACs, 43 and indeed, patient education has successfully increased adherence to other medications, including to warfarin. 33 , 44 However, studies focused on DOAC adherence are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Patient knowledge about the existence of reversal agents, the frequency of physician communication about these agents, and the influence of knowledge about the agents on adherence requires additional exploration, as does the relationship of these interventions on patient adherence. Qualitative work suggests that patients and providers support educating patients about DOACs, 43 and indeed, patient education has successfully increased adherence to other medications, including to warfarin. 33 , 44 However, studies focused on DOAC adherence are needed.…”
Section: Discussionmentioning
confidence: 99%
“…12,54,55 Educational programs typically focus on anticoagulation management; however, our study results suggest that this should be expanded to recognize VTE as a disease with many impacts. [56][57][58] Education and patient support are integral at all time points across a patient's VTE journey. Baddeley All authors revised and approved the final draft of the manuscript.…”
Section: Ack N Owled G M Entsmentioning
confidence: 99%
“…Many studies suggested that OACs in AF patients may also reduce the risk of cognitive decline and dementia (6). However, the optimal use of OACs requires proper patient education and engagement in the management of their condition (7). AF patients need to be aware of their condition, understand the risks and benefits of OACs, and adhere to the prescribed treatment regimen to achieve the best outcomes (8).…”
Section: Introductionmentioning
confidence: 99%